2021
DOI: 10.2478/hukin-2021-0025
|View full text |Cite
|
Sign up to set email alerts
|

In-Season Assessment of Sprint Speed and Sprint Momentum in Rugby Players According to the Age Category and Playing Position

Abstract: The purpose of this study was to investigate the interval in which male rugby union players reach maximum speed in a 50 m sprint according to age categories and playing positions. This study also aimed to establish the optimal distance for the assessment of sprint speed and to compare the differences in anthropometrics, sprint and sprint momentum according to the age and playing position. Three hundred amateur rugby players performed anthropometric and physical fitness tests (10, 20, 30, 40 and 50 m sprint tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 30 publications
(49 reference statements)
2
16
0
Order By: Relevance
“…This can be explained by the fact that at an older age, both positions accumulated enough sprint training to mitigate acceleration discrepancies on short distances. These findings on positional differences are in line with previous works (38,59) and indicate that if academy players attempt to be classified as a forward, they need to possess exceptional momentum characteristics over both 10 m and 20 m distances. Altogether, it is possible to say that academy RU players should possess an optimal combination of body mass and speed and that sprint momentum should be trained over 10 and 20 m regardless age and playing position.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This can be explained by the fact that at an older age, both positions accumulated enough sprint training to mitigate acceleration discrepancies on short distances. These findings on positional differences are in line with previous works (38,59) and indicate that if academy players attempt to be classified as a forward, they need to possess exceptional momentum characteristics over both 10 m and 20 m distances. Altogether, it is possible to say that academy RU players should possess an optimal combination of body mass and speed and that sprint momentum should be trained over 10 and 20 m regardless age and playing position.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, the purpose of this investigation was to evaluate these characteristics in an English Premiership RU academy across multiple age categories (i.e., U16, U18, and U21) and playing positions (i.e., forwards and backs). Similar to previous literature (11,59), key findings revealed how anthropometric (i.e., body mass and height) and physical (i.e., power, momentum and aerobic capacity) characteristics differed across the three age groups. Results based on positional differences showed forwards were generally heavier, taller, stronger, more powerful, and more disruptive when compared to backs.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The players were also instructed not to make any type of backward movement with their upper body or feet, so as not to inadvertently trigger the first timing gate. This distance was selected, because it has been reported as the optimal distance to assess maximum sprint speed [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…For example, forwards are usually heavier, taller, and exhibit a greater body fat percentage than backs (7,9,13). Moreover, previous research (7) in young rugby players reported greater sprint velocities for backs compared with forwards, in different split distances from 10 to 40 m, with maximum velocity ( V max ) being a discriminant factor across age categories (7,31). Regarding strength, published data indicate that forwards possess greater absolute values in comparison to backs, which may be partially explained by their larger body mass (BM) (29,32).…”
Section: Introductionmentioning
confidence: 94%